Changes in nutritional management after gastrointestinal cancer surgery over a 12-year period: a cohort study using a nationwide medical claims database - Yoshikuni Kawaguchi; Kenta Murotani; Nahoki Hayashi; Satoru Kamoshita (BMC Nutrition)
Abstract Background Nutritional management in patients after gastrointestinal cancer surgery has changed throughout the 2000s. However, its evolution has not been formally studied. This study aimed to evaluate changes in nutritional management using real-world data. Methods Patient data from 2011 to 2022 were extracted from a nationwide medical claims database. Patients were divided into four groups based on their year of hospital admission: period I, 2011–2013; II, 2014–2016; III, 2017–2019; IV, 2020–2022. For each period, feeding routes in all patients and prescribed doses of parenteral energy and amino acids in fasting patients during postoperative days (POD) 1–7 were determined. The results of the four different periods were compared using statistical trend tests. Results The study cohort was comprised of 365,125 patients. During POD 1–3, the proportion of patients administered any oral intake increased over time (I, 40.3%; II, 47.1%; III, 49.4%; IV, 54.2%; P < 0.001), while that of patients receiving parenteral nutrition (PN) decreased (I, 60.1%; II, 55.0%; III, 50.3%; IV, 45.5%; P < 0.001). Of 19,661 patients with PN alone (i.e., neither oral intake nor enteral nutrition) during POD 1–7, the median (interquartile range) prescribed doses on POD 7 of energy (kcal/kg) [I, 15.3 (10.3–21.9); II, 13.9 (8.4–20.0); III, 13.2 (7.7–19.2); IV, 12.9 (7.0–18.7); P < 0.001] and amino acids (g/kg) [I, 0.65 (0.30–0.94); II, 0.58 (0.24–0.89); III, 0.56 (0.00–0.86); IV, 0.56 (0.00–0.87); P < 0.001] both decreased over time. Conclusion From 2011 to 2022, more patients who underwent gastrointestinal cancer surgery in Japan were administered early oral intake, while fewer patients were administered early PN. Overall, the energy and amino acid doses prescribed in PN were far below the guideline recommendations.